Genetic and environmental effects on processing productivity and food product yield: drudgery of women's work - Bello, A.A.; Agbona, A.; Olaosebikan, O.; Edughaen, G.; Dufour, D.; Bouniol, A.; Iluebbey, P.; Ndjouenkeu, R.; Rabbi, I.Y.; Teeken, B. (Wiley, 2024)
Background Cassava processing is a crucial source of livelihood for rural farmers and processors in Nigeria and Cameroon. This study investigated the varietal effect on the processing productivity of women farmer processors within their working environment and compared this to the field yield and the food product quality as evaluated by the processors. Field trials were established in Nigeria (Benue and Osun state) and Cameroon (Littoral zone). Eight cassava genotypes, including improved, regional, and processors' preferred checks were evaluated. Roots of these genotypes were harvested, and processed into gari and eba by processors with the time of each processing step recorded. Through pairwise ranking processors assessed the quality of the roots and food products.